Wafer‐Scale 2H‐MoS2 Monolayer for High Surface‐enhanced Raman Scattering Performance: Charge‐Transfer Coupled with Molecule Resonance. Issue 8 (10th April 2022) - An, Keyu; Chen, Mingpeng; He, Bingchen; Ai, Haoqiang; Wang, Wei; Zhang, Zhihong; Pan, Zhongbin; Chen, Shi; Ip, Weng Fai; Lo, Kin Ho; Chai, Jianwei; Wang, Shijie; et al.
Abstract: The surface‐enhanced Raman scattering (SERS) as a novel and efficient analytic technique to probe molecules has attracted tremendous attention. Semiconducting substrates have been widely investigated for their applications into SERS because of their easy integration with electronic devices. In this work, a wafer‐scale semiconducting MoS2 monolayer (2H‐MoS2 ‐ML) without additional treatment is used as the SERS substrate, which shows the naturally formed MoS2 ML has excellent chemical stability, high uniformity, and high sensitivity. It is found that the detection concentration limit can reach 1 × 10 −8 m and the enhancement factor is about 4.5 × 10 6 for the rhodamine 6G (R6G) under a 532 nm excitation laser, which is the highest SERS performance observed on 2H‐MoS2 ‐ML up to now. The experimental and computational studies reveal that the photo‐enhanced charge transfer coupled with molecule resonance contribute to remarkable SERS. In addition to R6G, 2H‐MoS2 ‐ML shows good SERS signals on the detection of amaranth and crystal violet too. The findings not only provide an insightful understanding of the mechanism for the improved SERS performance of semiconducting transition‐metal dichalcogenides (TMDs) MLs, but are helpful for the design of novel SERS substrates. It is expected that the wafer‐scale TMDs may find practical applications in SERS. Abstract : A wafer‐scale 2H‐MoS2 monolayer without additional treatment is used as surface enhanced‐Raman scattering substrate. The detection limit can reach 1 × 10 −8 m for R6G under a 532 nm excitation, and the lowest detection limit can be held even after 28 days. This study shows the naturally formed MoS2 ML has excellent chemical stability, high uniformity, and high sensitivity.